Use of Scanning Electrochemical Microscopy as a Predictive Technique in Salt Spray Corrosion Testing.
By using scanning electrochemical microscope (SECM) to predict the results of salt spray corrosion test, the problem of long salt spray corrosion test in the prior art is solved, and the rapid and reliable prediction of corrosion protection treatment effect is achieved.
Patent Information
- Application Number
- JP2022554668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-12
- Filing Date
- 2021-03-12
- Publication Date
- 2025-04-28
- Estimated Expiration
- 2041-03-12
AI Technical Summary
The existing salt spray corrosion testing methods take a long time and cannot quickly predict the effect of metal surface corrosion protection treatment, resulting in products that fail to meet the specifications during the production process, resulting in waste of resources.
Scanning electrochemical microscopy (SECM) is used as a prediction technology, and local analysis of the surface is performed, and the surface is scanned by ultramicroelectrodes to measure current changes, thereby predicting the results of salt spray corrosion test.
It realizes rapid and reliable prediction of the corrosion protection effect of metal surfaces, can obtain analysis results in a short time, avoids long waits for salt spray corrosion tests, and improves production efficiency.
Smart Images

Figure 0007669382000003 
Figure 0007669382000004 
Figure 0007669382000005
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of analyzing and characterizing surfaces by electrochemistry.
[0002] More specifically, the present invention relates to the use of Scanning Electrochemical Microscopy (hereinafter more simply referred to as SECM, and the same acronym is used for the technique and the apparatus) as a predictive technique for salt spray corrosion testing.
[0003] Applications of the present invention can be found in all sectors of activity where salt spray corrosion testing is used, whether in industrial sectors such as the automotive, aviation, aerospace, railway, wind energy, construction and public works sectors, or in research and development laboratories working on corrosion mechanisms or the development of anticorrosive coatings, or even in laboratories specialized in the analysis and characterization of materials. [Background technology]
[0004] The salt spray corrosion test (neutral, acetic acid, or copper acetate), more simply called the "salt spray test", is a test that makes it possible to evaluate the corrosion resistance of metallic materials, whether they have or do not have a coating that protects them against corrosion, whether it is temporary or permanent.
[0005] These tests are essential in sectors where metal parts are ubiquitous.
[0006] The performance of salt spray tests is described in various standards (ASTM B117-19, NF EN ISO 9227 / 2017, IEC 60068-2-11, etc.). In all cases, the part whose corrosion resistance it is desired to evaluate is placed in a test chamber in which a solution containing either sodium chloride (neutral salt spray), or a mixture of sodium chloride and acetic acid (acetate salt spray), or even a mixture of sodium chloride, acetic acid and cupric chloride (copper acetate salt spray) is sprayed continuously under defined temperature and pressure conditions, the principle being to expose the part to a controlled corrosive environment.
[0007] Corrosion resistance is assessed by periodic monitoring for signs of corrosion, typically in the form of pitting.
[0008] Depending on the type of test part, the duration of this monitoring varies and can range from one week to several weeks, which can be long and disadvantageous on an industrial scale.
[0009] Thus, for example, if parts made from an aluminum alloy that has been treated with a conversion treatment, such as trivalent chromium, are subjected to a salt spray test, and a failure occurs during the protection treatment that causes uncontrolled conversion (insufficient concentration of the conversion bath, too short duration of immersion of the parts in the conversion bath, etc.), it is only at the end of the salt spray test (i.e., more than one week after the test began) that it is discovered that the treated parts do not meet specifications. These parts are therefore unsalable and must be scrapped, as should all other parts that have been treated with the same conversion treatment for the duration of the salt spray test. Thus, a waste of time and money.
[0010] It would therefore be desirable to have a technique that makes it possible to predict the results of a salt spray test in a rapid and highly reliable manner, so that possible defects can be rectified during the production of the metal part or during the implementation of a corrosion protection treatment on its surface, without having to wait for the metal part to be subjected to the salt spray test.
[0011] However, to date, no such technology exists.
[0012] What do exist are prediction protocols by electrochemical impedance. However, electrochemical impedance is an electrochemical technique and its results are averaged over the entire surface examined. The measured impedance therefore characterizes the average surface state, combining the contributions of both well-protected and more vulnerable areas, and is not suitable for studying localized corrosion phenomena. In addition, electrochemical impedance requires the use of complex mathematical models to process the data, which makes it difficult to consider applications in industrial environments. Localized impedance methods exist, but are anyway complicated to implement.
[0013] Also present is the method of Tafel lines, a method traditionally used in R&D to evaluate the current and corrosion potential of metallic materials. However, this method also has some drawbacks. Indeed, the tests are difficult to reproduce, especially for complex alloys such as the Al2024 aluminum alloy. They require the surface to be examined to be polarized, which induces the stimulation of the passivation layer and causes a modification of the state of this surface. In the literature, the surface to be examined is generally exposed to a saline solution that can trigger corrosion phenomena before carrying out the measurements. Moreover, as in the case of the electrochemical impedance method described above, the measurements carried out by the Tafel lines method are averaged over the entire surface examined. Finally, the interpretation of the obtained polarization curves, and in particular the plotting of the tangents, are potential sources of additional errors.
[0014] There have been some unusual studies published in which SECM and salt spray tests have been used within the same study.
[0015] These studies are as follows: - Jiang Mei-Yan et al. (Corrosion Science 2015, 92, pp. 118-126, hereafter [1]), on the ability of silanes to improve the corrosion protection properties of epoxy resins on 2024 aluminum alloy substrates. - Junsheng Wu et al. (Materials 2017, 10(4), p. 426, hereafter [2]), on the corrosion protection effect of decavanadate hydroxide-based coatings on 2024 aluminum alloy substrates. - Dongdong Peng et al. (Journal of Coatings Technology and Research 2016, 13, pp. 837-850, hereafter [3]), on the corrosion protection properties of zirconium-based coatings on 6061 aluminum alloy substrates. - Yi Xiao et al. (Arabian Journal for Science and Engineering 2018, 43(7), pp. 3577-3584, hereafter ref. [4]), on the corrosion resistance of zinc coatings modified with silica nanoparticles. - Peng Guangchun et al. (Progress in Organic Coatings 2020, 140, pp. 1-10, hereafter [5]) on the ability of metal hydroxides to enhance the anticorrosive properties of epoxy varnishes on carbon steel substrates.
[0016] In all these publications, the authors use SECM and salt spray testing as complementary and not interchangeable investigative techniques, where SECM is used to understand the mechanisms by which the coatings investigated are likely to protect against corrosion, and salt spray testing is used to check whether the coatings investigated actually have a corrosion protection effect.
[0017] It should also be noted that in references [2] and [5], the SECM analysis and the salt spray test are not performed on the same specimens, but on specimens that have been intentionally scratched beforehand for this purpose, whereas the specimens subjected to the salt spray test do not have any scratches.
[0018] In references [1] to [5], no correlation has been established between SECM and salt spray tests, apart from the fact that the results of these two investigation techniques, as well as those of other investigation techniques such as electrochemical impedance spectroscopy, can contribute to the confirmation of the ability of a coating to protect a substrate against corrosion (see point "4. Discussion" in reference [1]).
[0019] In addition, it is never stated or even suggested in the literature [1] to [5] that the duration of the salt spray test is a disadvantage, that it would therefore be desirable to be able to eliminate the need to carry out this type of test, and that SECM, being a local analytical technique, is likely to be used instead of salt spray testing, which itself belongs to a global analytical technique. [Prior art documents] [Non-patent literature]
[0020] [Non-Patent Document 1] Jiang Mei-Yan et al., Corrosion Science 2015, 92, pp. 118-126 [Non-Patent Document 2] Junsheng Wu et al., Materials 2017, 10(4), 426 [Non-Patent Document 3] Dongdong Peng et al., Journal of Coatings Technology and Research 2016, 13, pp. 837-850 [Non-Patent Document 4] Yi Xiao et al., Arabian Journal for Science and Engineering 2018, 43(7), pp. 3577-3584 [Non-Patent Document 5] Peng Guangchun et al., Progress in Organic Coatings 2020, 140, pp. 1-10 Summary of the Invention [Problem to be solved by the invention]
[0021] The present invention aims to overcome the drawbacks of the state of the art by proposing to use SECM as a predictive technique for salt spray corrosion tests applied to surfaces with corrosion protection treatments.
[0022] In other words, the present invention proposes the use of SECM to predict the corrosion resistance results that would be obtained for a surface S1 that has been subjected to a corrosion protection treatment, if the surface S1 is subjected to a salt spray corrosion test, and this use involves the analysis of the surface S1 by SECM. [Means for solving the problem]
[0023] It is recalled that SECM is a microscopy technique that offers the possibility to electrochemically probe and image surfaces using a local probe, a miniaturized electrode called an ultramicroelectrode (or UME), which scans the surface.
[0024] As specified above, SECM is inherently a local analytical technique, which is known to be suitable for measuring local phenomena such as pitting corrosion of metal surfaces.
[0025] What is new, however, and totally unexpected, is that SECM provides information that represents the corrosion resistance of the entire surface, and therefore makes it possible to predict with a high degree of confidence what the outcome of a salt spray test applied to that surface will be.
[0026] SECM is conventionally implemented using equipment, a typical example of which is illustrated diagrammatically in Figure 1. As shown in this figure, the equipment (referenced as 1) includes: an electrochemical cell 10 provided to be filled with an electrolyte 15 in which, under operating conditions, the surface to be analysed 11, the probe 12, the counter electrode 13 and possibly the reference electrode 14 are immersed, a potentiostat, if, under operating conditions, a potential is intended to be applied to a single probe 12, or else a bipotentiostat 16, if, under operating conditions, a potential is intended to be applied to both the surface to be analyzed 11 and to the probe 12, as shown in FIG. 1; a system making it possible to displace the probe 12 and the surface 11 to be analyzed relative to one another in three directions (x, y and z) and to control this displacement, as well as a computer system 17 for acquiring and processing data, i.e. the current measured at the probe 12 while the probe 12 is scanning the surface 11 to be analysed.
[0027] Furthermore, a portable electrochemical microscope device in the form of a stylus has recently been developed by a team of researchers to which the present inventors belong, described in International Application WO2020 / 012097, hereafter document [6], which offers performances comparable to those of an instrument of the type shown in Figure 1, while making it possible to eliminate the constraints imposed by this instrument, and in particular by the limited dimensions of its electrochemical cell, as well as by the spatial requirements of the electrical and / or mechanical elements provided to this instrument to ensure and control the scanning.
[0028] Within the scope of the present invention, the SECM is preferably used in a "feedback" mode, denoted FD, also called regenerative mode.
[0029] However, it goes without saying that the SECM can also be used according to other modes, such as the following: - Redox competition (or RC) mode, in which the substrate (i.e. the surface to be analyzed) and the probe are polarized at the same potential and compete to carry out the same electrochemical reaction; - Substrate Generation / Tip Collection (or SG / TC) mode, in which the substrate generates electroactive species that are detected by the probe, and - Tip Generation / Substrate Collection (or TG / SC) mode, in which the probe generates electroactive species that are detected by the substrate.
[0030] In the feedback mode, it is recalled that the electrolyte contains both a salt that gives the solution ionic conductivity and a redox mediator that allows the redox reaction. The probe is polarized at a potential corresponding to the diffusion plateau of the redox mediator, inducing the oxidation of the redox mediator if it is in reduced form, or the reduction of this mediator if it is in oxidized form. Far from the surface to be analyzed, the species generated are free to diffuse towards the probe. However, - If the surface to be analyzed is made of an insulating material, and if a probe is brought close to this surface, the diffusion of the species generated is hindered by the surface, and the current measured by the probe decreases as the distance separating the tip of the probe from the surface decreases, i.e. this is called negative feedback. - If the surface to be analyzed is made of a conductive material, and if a probe is brought close to this surface, the diffusion of the species generated is also hindered, but these species can be regenerated by the surface (i.e. regenerated from an oxidized state and back to a reduced state or vice versa) and undergo oxidation or reduction reactions again, so that the current measured by the probe increases as the distance separating the tip of the probe and the surface decreases, i.e. positive feedback is seen.
[0031] According to the invention, the analysis of a surface S1 first involves scanning this surface with a probe, the tip of the probe being maintained at a constant distance d from the surface S1 during this scan.
[0032] In that case, when scanning, the tip of the probe preferably follows a trajectory that includes one or more straight line segments.
[0033] The trajectory followed by the probe tip may include only one straight line segment, in which case in the following reference is made to "line-scan" (or on-line-scan) SECM analysis.
[0034] Alternatively, the trajectory followed by the tip of the probe may comprise several straight line segments, advantageously parallel to one another, in which case reference is made below to SECM analysis by "mapping".
[0035] The analysis of the surface S1 may secondly involve the positioning of a probe at several points directly above this surface, the tip of the probe being disposed at a constant distance d from the surface S1 at each positioning point.
[0036] The positioning points of the probe are preferably selected randomly, in which case reference is made below to a "statistical" SECM analysis. This type of SECM analysis is particularly advantageous due to the speed with which it can be performed.
[0037] For statistical SECM analysis, the use of a handheld device such as that described in International Application No. WO2020 / 012097 is particularly recommended, insofar as this device makes it possible to ensure that at each positioning point the probe is sufficiently perpendicular to the surface to be analyzed, thereby ensuring that the distance d is fully taken into account, regardless of the configuration of the surface.
[0038] If the analysis of the surface S1 involves scanning this surface with a probe, this use preferably comprises at least a) selecting a point directly on the surface S1; b) moving the tip of the probe a distance d at the point selected in step a); and c) scanning the surface S1 with the probe from the point selected in step a) by maintaining the tip of the probe at a distance d and measuring the current in the probe as it scans.
[0039] If the analysis of a surface S1 involves the positioning of a probe at several points located directly above this surface, this use includes at least a) selecting a probe positioning point; and b) for each location point, moving the tip of the probe a distance d and measuring the current with the probe at each location point.
[0040] In both cases, the distance d is advantageously predetermined by establishing an approach curve.
[0041] As known per se, the establishment of an approach curve consists of placing the probe at infinity from the surface to be analyzed (i.e. at a distance from the surface high enough so that this surface does not affect the value of the current measured with the probe), then gradually approaching the probe to the surface, perpendicular to this surface (direction z), while measuring the current with the probe (which it is recalled will decrease or increase depending on the insulating or conductive nature of the surface) until the tip of the probe touches the surface and makes it possible to set the zero point of positioning of the tip of the probe. The probe is then lifted until its tip moves to the distance from the surface desired for the measurement, namely the distance d.
[0042] Typically, the distance d is between 1 / 10 of the diameter of the conductive part of the probe and the diameter of this conductive part. Thus, for example, for a probe consisting of a metal wire sealed in a glass capillary, the distance d is typically between 1 / 10 of the diameter of the metal wire and the diameter of this wire, i.e., between 5 μm and 50 μm if the wire diameter is 50 μm.
[0043] Also, as is known per se, the scanning of the surface S1 by the probe, or the positioning of the probe at a number of points directly above the surface S1, is carried out by a method in a horizontal plane (x,y) of surface S1 when the probe is then fixed in this horizontal plane, or it can be obtained by any displacement of the probe, if the surface S1 is then fixed in said horizontal plane.
[0044] Regardless of the manner in which the analysis of the surface S1 is carried out (analysis by mapping, analysis by line scanning or analysis by statistics), in the context of an industrial application of the invention, i) measuring the current with the probe at n1 different points of the surface S1 under preselected operating conditions (distance d, composition of the electrolyte, potential applied to the probe, if appropriate, potential applied to the surface S1, if appropriate, scanning speed of the probe) to obtain n1 current values, n1 being an integer at least equal to 5; ii) determining the percentage of the n1 current values obtained in step i) that are equal to or greater than a detection threshold D, any current value equal to or greater than D being deemed to correspond to a point of the surface S1 that is likely to corrode in the salt spray test; and iii) from the percentage obtained in step ii), determine the number of corrosion points N / unit area that is likely to be presented by surface S1 if subjected to a salt spray test, and use the number of corrosion points / unit area thus obtained as the maximum number of corrosion points N that surface S1 should have in order to successfully pass the salt spray test. max It is preferable to compare with / unit area.
[0045] This means: - N is N max It is possible to predict that the surface S1 will effectively pass this test if it is smaller than - N is N max If it is greater, it can be predicted that the surface will not pass this test successfully.
[0046] According to the invention, D is preferably predetermined by measuring the current with the probe used in step i) at n2 points different from a reference surface S2 that is free of corrosion and cannot be corroded by the salt spray test under the operating conditions used in step i), obtaining n2 current values, where n2 is an integer at least equal to 2, calculating the average of the n2 obtained current values, and selecting a current value that is, for example, 10%, 15% or 20% higher than the average value but lower than the highest of the n2 current values.
[0047] However, D may be predetermined in some other way. D may correspond to a current value that is, for example, 110% or more higher than the highest of the n2 current values measured on the reference surface S2, or - D may be selected based on the expected current value for the probe and operating conditions used in step i) if this probe and these operating conditions have already been used to analyse one or more surfaces other than surface S1 by SECM.
[0048] The reference surface S2 may be a surface of the same nature as surface S1 (e.g. made from the same material and subjected to the same corrosion protection treatment), but this is not mandatory, what is important is that surface S2 has the same roughness as surface S1 and is not or cannot be corroded by the salt spray test. It may therefore in particular be a surface of a commercially available test specimen, or a surface from the same production line as surface S1, but which is checked beforehand as not being likely to be corroded by the salt spray test.
[0049] In step iii), the determination of N preferably involves the correlation of this percentage with a percentage P previously obtained for a reference surface S3 subjected to both an analysis by SECM and a salt spray test, whereas the percentage P has been determined by measuring the current with the probe used in step i) under the operating conditions used in step i) at n3 different points of the surface S3 to obtain n3 current values, n3 being an integer at least equal to 5, and by determining the percentage of the n3 values that are greater than D, - On the other hand, it has been established that the percentage P corresponds to the number of corrosion spots / unit area revealed by the salt spray test.
[0050] N can therefore be determined in particular by dividing the percentage obtained in step ii) by P and multiplying the quotient of this division by the number of corrosion spots / unit area revealed on surface S3 by the salt spray test.
[0051] If the salt spray test for which it is desired to predict the results is a test that meets a standard such as ASTM B117-19, NF EN ISO 9227 / 2017, or IEC 60068-2-11 test, N max is given by this standard.
[0052] Furthermore, if the invention is implemented to predict for several surfaces the corrosion resistance results that would be obtained if these surfaces were subjected to the same type of salt spray test, the detection threshold D and the percentage P may be determined as final and used for all surfaces, provided, of course, that the analysis by SECM of said surfaces is carried out with the same probe and under the same operating conditions as those used to determine this detection threshold and this percentage.
[0053] In the above, the expression "current measured by the probe" preferably, but not necessarily, refers to the normalized current I / I inf where I is the current measured by the probe at a distance d from the surface, and I inf is the current measured by the probe when it is at an infinite distance from the surface.
[0054] According to the invention, the analysis of the surface S1 is preferably carried out using an electrolyte which contains a redox mediator in the reduced state.
[0055] Such mediators include, for example, ferrocyanide (Fe(CN)6 4- ), ferrocene (FcCp2), decamethylferrocene (Me 10 (FcCp2)) or ferrocenedimethanol (Fe(MeOH)2).
[0056] However, it will be appreciated that electrolytes containing redox mediators in their oxidized state are also likely to be used.
[0057] As is known per se, the electrolyte may be in liquid form, but if the SECM is carried out in a portable device, it may also be in the form of a gel.
[0058] When the electrolyte is in liquid form, it is advantageously either an aqueous or organic solution containing, in addition to the redox mediator, at least one compound capable of ionizing in solution, such as a mineral or organic salt, or an ionic liquid.
[0059] When the electrolyte is in the form of a gel, it is advantageously a gel obtained by adding a gelling agent such as gelatin, pectin, agar, alginate, gum arabic, xanthan gum, carrageenan or similar to an aqueous or organic solution or an ionic liquid as defined above.
[0060] The salts may in particular be metal salts, in particular alkali metal salts such as sodium chloride or potassium chloride.
[0061] The present invention has many advantages. In fact, it makes it possible to predict in a very reliable manner what the salt spray test and its results will be, thanks to the following analysis: - the results of said analysis are obtained quickly (within an hour for samples analyzed by mapping and within a few minutes for samples analyzed by line scanning); - the analysis can be carried out both on a control sample of the part and on the part itself, for example when a portable device such as that described in International Application No. WO 2020 / 012097 is used; - The analysis can also be carried out on all types of materials whose corrosion resistance is likely to be analyzed by salt spray testing.
[0062] Other features and advantages of the present invention will become apparent from the following additional description relating to implementations of the present invention that enable verification.
[0063] Of course, this additional description is given only by way of illustration of the subject matter of the present invention and in no way constitutes a limitation thereof. [Brief description of the drawings]
[0064] [Figure 1] FIG. 1 illustrates, as already commented, a schematic of a typical example of SECM equipment as used in laboratories. [Diagram 2] FIG. 1 shows the results of a SECM analysis with mapping as obtained on a non-anodized Al2024 aluminum alloy sample. [Diagram 3] FIG. 1 shows the results of a SECM analysis with mapping for an anodized Al2024 aluminum alloy sample. [Figure 4] FIG. 1 is a front view of a non-anodized Al2024 aluminum alloy specimen taken after 168 hours of neutral salt spray testing. [Diagram 5] FIG. 1 is a front view of an anodized Al2024 aluminum alloy specimen taken after 168 hours of neutral salt spray testing. [Figure 6]FIG. 2 shows the results of an SECM analysis by line scan as obtained on the one hand for a non-anodized Al2024 aluminium alloy sample (curve 1) and on the other hand for an anodized Al2024 aluminium alloy sample (curve 2), in which the vertical axis corresponds to the normalized current I / Iinf measured by the probe and the horizontal axis corresponds to the distance D, expressed in μm, travelled in a straight line by the probe. [Figure 7] 1 is an image taken under an optical microscope of a first sample of Al2024 aluminum alloy treated with trivalent chromium conversion corrosion protection. [Figure 8] 1 is a SEM image of a second sample of Al2024 aluminum alloy that has been treated with a trivalent chromium conversion corrosion protection treatment. [Figure 9] FIG. 1 shows three polarization curves, denoted 1, 2, and 3, respectively, obtained by performing three successive cyclic voltammetry tests on the same sample of Al2024 aluminum alloy, previously protected by trivalent chromium conversion, as well as the Tafel lines plotted from these curves, in which the vertical axis corresponds to the logarithm of the absolute value of the current, denoted log|I|, and the horizontal axis corresponds to the potential, denoted E, expressed in volts, applied to the aluminum alloy sample. [Figure 10] FIG. 1 shows a front view of an Al2024 aluminum alloy specimen, previously protected by trivalent chromium conversion, after the specimen had been subjected to three successive cyclic voltammetry tests. [Figure 11] FIG. 3 shows polarization curves 3 and 4, respectively, obtained by performing cyclic voltammetry tests on two different samples of Al2024 aluminum alloy previously protected by trivalent chromium conversion, as well as the Tafel lines plotted from these curves, in which the vertical axis corresponds to the logarithm of the absolute value of the current, denoted log|I|, and the horizontal axis corresponds to the electric potential, denoted E, expressed in volts, applied to the aluminum alloy samples. [Figure 12]FIG. 1 shows the results of three SECM analyses by line scan, denoted 1, 2 and 3 respectively, carried out on the same area of an Al2024 aluminium alloy specimen previously protected by trivalent chromium conversion, in which the vertical axis corresponds to the normalised current I / Iinf measured by the probe during each analysis and the horizontal axis corresponds to the distance D, expressed in μm, travelled by the probe. [Figure 13] FIG. 2 shows the results of an SECM analysis with mapping as obtained on a first sample of Al2024 aluminium alloy previously protected by trivalent chromium conversion. [Figure 14] FIG. 1 shows the results of an SECM analysis with mapping as obtained on a second sample of Al2024 aluminium alloy previously protected by trivalent chromium conversion. [Figure 15] FIG. 2 is a front view of a first sample of Al2024 aluminum alloy pre-treated for corrosion protection by trivalent chromium conversion as taken after 168 hours of neutral salt spray testing. [Figure 16] FIG. 1 is a front view of a second sample of Al2024 aluminum alloy pre-treated for corrosion protection by trivalent chromium conversion as taken after 168 hours of neutral salt spray testing. [Figure 17] FIG. 13 shows the results of an SECM analysis with mapping as obtained on a third sample of Al2024 aluminium alloy previously protected by trivalent chromium conversion. [Figure 18] FIG. 13 shows the results of the SECM analysis with statistics as obtained for a third sample of Al2024 aluminium alloy previously protected by trivalent chromium conversion, in which the vertical axis corresponds to the number of iterations N and the horizontal axis corresponds to the normalised current I / Iinf measured by the probe. [Figure 19] FIG. 11 is a front view of a third sample of Al2024 aluminum alloy pre-treated for corrosion protection by trivalent chromium conversion as taken after 168 hours of neutral salt spray testing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS EXAMPLES
[0065] Prediction from SECM analysis by mapping to reference samples Two samples of Al2024 aluminium alloy, one anodised and one non-anodised respectively, whose corrosion resistance is known and which can therefore be used as a reference, are subjected to SECM analysis by mapping, using the following operating conditions: - Probe: UME consisting of a platinum wire of 12 cm length and 50 μm diameter sealed in a glass capillary; - Reference electrode: Ag / AgCl, - Counter electrode: gold, - an electrolyte containing potassium chloride as salt and 1 mmol / L ferrocenedimethanol (Fe(MeOH)2) as redox mediator; - Potential applied to the probe by the potentiostat: 0.6 V; - Potential applied to the sample: None (OCP mode), - Distance d (probe tip / sample surface): 10 μm, - Probe surface scanning speed: 10μm / s.
[0066] The anodized alloy has a protective layer made of aluminum oxide about 8 μm thick, which confers high corrosion resistance.
[0067] The non-anodized alloy itself has low corrosion resistance.
[0068] The maps obtained for each of the two alloy samples are illustrated in Figures 2 and 3, where Figure 2 corresponds to the non-anodized alloy sample and Figure 3 corresponds to the anodized alloy sample. At the right edge of these figures, the normalized current (I / I inf ) is shown, which is the scale of the current I actually measured by the probe while scanning the sample surface, and the current I measured by the probe when the tip of the probe is infinitely far from the sample surface. inf This corresponds to the ratio of
[0069] As shown in these figures, the maps acquired for the non-anodized alloy specimen reveal that the specimen has a uniformly high surface conductivity (I / I inf >0.9), so that the surface of this sample may be sensitive to pitting corrosion, whereas maps obtained for the anodized alloy sample show that this sample, conversely, has a uniformly low surface conductivity (I / I inf <0.4), which provides an a priori proof of the passivation quality of the protective layer contained in this sample.
[0070] To check whether these maps allow the prediction that the salt spray test will reveal that only the anodized alloy samples are suitable, samples of both types of alloy are subjected to a salt spray test under the following conditions: - Neutral salt spray (NaCl solution), - Temperature and pressure throughout the test chamber: 35°C - 1 bar; - NaCl concentration in the spray solution: 50 g / L; - inlet flow rate of the solution sprayed into the test chamber: 1.8 L / h; - flow rate of recovered spray solution (condensate): 2mL / h; - Test duration: 168 hours.
[0071] The results of these tests are presented below in Table I and in Figures 4 and 5, where Figure 4 corresponds to a non-anodized alloy sample and Figure 5 corresponds to an anodized alloy sample.
[0072] Pitting corrosion / dm below 2.5 after 168 hours exposure to salt spray according to standard NF EN ISO 9227 2 Note that a given object is considered conforming if it has
[0073] [Table 1]
[0074] The table and these figures show that the results of the salt spray tests are in full agreement with the predictions obtained by SECM tests in mapping mode, thus confirming the feasibility of using SECM as a predictive technique for salt spray tests.
[0075] Importantly, while the salt spray test results had to be waited for seven days, the SECM mapping analysis itself was carried out in just half a day. EXAMPLES
[0076] Prediction by SECM analysis using line scan on reference sample To check whether this mode of performing SECM analysis, which is faster than mapping, also makes it possible to reliably predict the salt spray test results, two samples of Al2024 aluminium alloy, one anodised and one non-anodised, tested in Example 1 above, are also subjected to a line-scan SECM analysis.
[0077] These analyses are carried out using the same operating conditions as given in Example 1 above.
[0078] These results are shown in FIG.
[0079] In this figure, curve 1, which corresponds to the non-anodized alloy specimen, shows a very high feedback (I / I inf is close to 1). This also shows that the normalized current I / I inf reveals significant variations in the surface area, indicating the presence of corrosion spots.
[0080] Conversely, curve 2, which corresponds to the anodized aluminum alloy specimen, shows very low feedback (I / I inf is essentially equal to 0.3), further indicating no variation in surface conductivity.
[0081] These results are therefore in full agreement with the maps shown in Example 1 above, demonstrating that the use of line-scan SECM makes it possible to obtain prediction results that are just as relevant as those obtained by mapping SECM. EXAMPLES
[0082] Prediction of SECM analysis by mapping to samples protected by trivalent chromium conversion To demonstrate the industrial interest of the present invention, a series of analyses (SEM, Tafel lines, salt spray test, SECM analysis) were performed on Cr, instead of a reference sample as in Examples 1 and 2 above. III The present study was carried out on two series of Al2024 aluminum alloy specimens, hereafter referred to as series 3 and 4, which were corrosion-protected by chemical conversion.
[0083] In fact, this type of corrosion protection treatment, to date, is still not as well controlled as anodizing, so that each batch of treated parts results in parts with different corrosion resistance, so that salt spray tests are still essential today to check whether these parts are compliant.
[0084] 3.1Cr III Chemical anti-corrosion treatment Cr III The corrosion protection process is carried out in three steps: - a first step consisting of immersing the alloy specimen for 5 minutes in a bath containing 40% by volume of Socosurf® 1858, 10% by volume of Socosurf® 1806 and 50% demineralised water, maintained at 50°C under stirring, followed by rinsing the specimen with distilled water; - a second step consisting of immersing the alloy specimen for 10 minutes in a bath containing 35% by volume of Socosurf™ TCS and 65% by volume of demineralized water, maintained at 40°C under stirring, and then rinsing the specimen with demineralized water; and - a third step consisting of immersing the alloy specimens for 5 minutes in a bath containing 10% by volume of Socosurf™ PACS, 6% by volume of hydrogen peroxide (H2O2) at 35% and 8% by volume of demineralised water, maintained at ambient temperature under stirring, then rinsing the specimens with demineralised water and finally drying with compressed air.
[0085] After this treatment, all samples have, as a rule, a protective layer made mainly of chromium and zirconium oxides with a thickness of about 200 nm.
[0086] 3.2 Analysis of samples by optical microscopy As shown in Figures 7 and 8, which correspond to images of the surface of a sample from series 3 (Figure 7) and the surface of a sample from series 4 (Figure 8), no differences between the surfaces of these two samples are detectable by optical microscopy. The corrosion protection layers of these two samples appear to have a similar morphology.
[0087] 3.3 Tafel line method Cyclic voltammetry tests are performed on samples belonging to series 3 and 4 in order to plot and utilize the Tafel lines, since this characterization method is commonly used in R&D to evaluate the current and corrosion potential of metallic materials.
[0088] These tests are performed using the following operating conditions: - Working electrode: Cr III A sample of Al2024 aluminum alloy that was treated for corrosion protection by chemical conversion. - Reference electrode: Ag / AgCl, - Counter electrode: gold, - Electrolyte: KCl 0.1mol / L, - Scanning speed: 10mV / s.
[0089] * Successive cyclic voltammetry tests on the same samples from series 4 Three cyclic voltammetry tests are performed consecutively on the same sample from series 4.
[0090] The polarization curve log|I|=f(E) and also the Tafel lines are then plotted.
[0091] The results are shown in FIG. 9, where curves 1, 2, and 3 correspond to the first, second, and third cycles, respectively.
[0092] As shown in this figure, very different results are obtained for each cycle, highlighting the evolution of the sample surface during the operation: the passivation layer is stimulated by the polarization of the sample during the measurement, leading to a modification of its surface state.
[0093] Moreover, these modifications are visible to the naked eye, as shown in Figure 10, a photograph of the surface of the sample taken at the end of the third voltammetric cycle, where darkened areas are visible in the exact location where the measurements were performed.
[0094] * Cyclic voltammetry tests on samples from series 3 and 4 Cyclic voltammetry tests were carried out on samples from each of series 3 and 4, with the aim of checking whether the Tafel line method makes it possible to distinguish the corrosion resistance of the protective layers of these samples.
[0095] Again, the polarization curve log|I|=f(E) and the Tafel lines are then plotted.
[0096] The results are shown in FIG. 11, where the curves are labeled 3 and 4 according to the series to which the samples belong, respectively.
[0097] As can be seen from this figure, very similar results are obtained for these two samples (very close corrosion potentials and currents).
[0098] However, as highlighted in point 3.5 below, salt spray tests on these two samples give very different results, highlighting that the use of Tafel lines via cyclic voltammetry is not an appropriate method to distinguish between two samples with different corrosion resistance despite being subjected to the same type of corrosion protection treatment.
[0099] 3.4 SECM analysis * SECM analysis by linescan on the same sample from series 4 Samples from series 4 were subjected to three successive SECM analyses by line scan, the three analyses being carried out on the same area of the sample and using the same operating conditions as described in Example 1.
[0100] The results are shown in FIG. 12, where curves 1, 2, and 3 correspond respectively to the first, second, and third scans of the sample area by the probe.
[0101] As shown in this figure, curves 1, 2, and 3 are nearly identical, which means that the SECM analysis does not cause any alteration of the sample surface.
[0102] * SECM analysis with mapping for samples from series 3 and 4 SECM analysis with mapping is carried out on samples belonging to series 3 and 4 using the same operating conditions as described in example 1.
[0103] The maps acquired for samples from each of the two series are illustrated in Figures 13 and 14, where Figure 13 corresponds to a sample from series 3 and Figure 14 corresponds to a sample from series 4. At the right edge of each of these figures is the normalized current I / I measured at the probe. inf The scale of values is shown.
[0104] These maps show that the samples from Series 4 have a uniformly higher surface conductivity (I / I inf≈0.7), thus indicating that the surface of this sample may have a higher sensitivity to corrosion. The map of the sample from series 4 further reveals more conductive areas potentially susceptible to pitting corrosion.
[0105] The samples from series 3 themselves have a uniformly low surface conductivity (I / I inf ≈0.4), proving the passivation quality of the corrosion protection layer of this sample.
[0106] These obtained maps show that the results of the salt spray test are different for the alloys of the two series, the alloys from series 3 have a higher and certainly higher quality corrosion resistance, while the alloys from series 4 have a lower corrosion resistance (however, this corrosion resistance is within the range of I / I inf should be superior to those of the untreated Al2024 alloy obtained --see Examples 1 and 2).
[0107] As a result, the predictions are as follows: - Alloys from Series 3 are suitable for salt spray, - Alloys from Series 4 onwards are incompatible with salt spray.
[0108] 3.5 Salt spray test Samples from Series 3 and Series 4 are subjected to a 168 hour salt spray test under the same operating conditions as described in Example 1 above.
[0109] The results of these tests are presented below in Table II and in Figures 15 and 16, where Figure 15 corresponds to samples from Series 3 and Figure 16 corresponds to samples from Series 4.
[0110] [Table 2]
[0111] This table and these figures confirm the predictions made above, thereby confirming that the corrosion diagnostics performed by SECM are extremely reliable. EXAMPLES
[0112] Prediction using statistical SECM analysis Statistical SECM analysis is carried out on samples of Al2024 aluminum alloy, previously protected by trivalent chromium conversion.
[0113] The operating conditions used are identical to those described in Example 1, with the slight difference that the probe is not scanned over the surface of the sample, but is instead positioned at different points located directly above the surface of the sample, the tip of the probe being 10 μm away from said surface at each positioning point, these points being randomly selected by a computer program developed for this purpose.
[0114] For comparison, a SECM analysis with mapping is also performed on the same samples.
[0115] The results of these two analyses are shown in Figures 17 and 18, where Figure 17 corresponds to the map obtained by the analysis in mapping mode, and Figure 18 corresponds to the normalized current I / I measured by the probe during the analysis in statistical mode. inf Corresponds to the classification of values.
[0116] These figures highlight the agreement that exists between the results obtained by mapping and by statistics, both of which show that the surface conductivity of the samples is generally high and the values I / I inf is between 0.7 and 0.8, which makes it possible to predict that the sample will be considered non-compliant at the end of the salt spray test.
[0117] Therefore, the samples are subjected to a 168 hour salt spray test under the same operating conditions as described in Example 1 above.
[0118] The results of this test are illustrated in FIG. 19, which shows a significant number of pitting corrosion (50 / dm 2 ) and confirms the non-compliance of the sample and thereby the predictive value of the statistical SECM analysis. [Explanation of symbols]
[0119] 10 Electrochemical Cell 11 Surface to be analyzed 12 Probe 13 Counter electrode 14 Reference electrode 15 Electrolytes 16 Bipotentiostat 17 Computer Systems
Claims
1. 1. Use of scanning electrochemical microscopy to predict the corrosion resistance result that would be obtained for a surface S1 that has been subjected to a corrosion protection treatment if the surface S1 were subjected to a salt spray corrosion test, comprising: analyzing the surface S1 by scanning electrochemical microscopy, the analysis comprising: i) measuring current with a scanning electrochemical microscopy probe at n 1 distinct points of said surface S1 under preselected operating conditions to obtain n 1 current values, where n 1 is an integer greater than or equal to 5; ii) determining the percentage of the n 1 current values obtained in step i) that are equal to or greater than a detection threshold D, any current value equal to or greater than D being deemed to correspond to a point of the surface S1 that is likely to corrode in a salt spray test; iii) determining from the percentage obtained in step ii) the number of corrosion points N / unit area likely to be presented by said surface S1 when subjected to a salt spray test and comparing the number of corrosion points / unit area thus obtained with the maximum number of corrosion points Nmax / unit area that said surface S1 should have in order to successfully pass the salt spray test, If N is less than Nmax, it is possible to predict that the surface S1 will effectively pass the test, if N is greater than Nmax, it is possible to predict that the surface S1 will not pass the test successfully; The use of scanning electrochemical microscopy, including
2. The use according to claim 1 , wherein the analysis of the surface S1 is carried out in a feedback mode.
3. 3. The use according to claim 2, wherein the analysis of the surface S1 comprises scanning the surface S1 with the scanning electrochemical microscopy probe, the tip of the probe being maintained at a constant distance d from the surface S1 as the surface is scanned.
4. The use according to claim 3 , wherein the tip of the probe, when scanning the surface S1, follows a trajectory that includes one or more straight line segments.
5. The use according to claim 4 , wherein the tip of the probe, when scanning, follows a trajectory that includes several straight line portions that are parallel to one another.
6. The analysis of the surface S1 comprises at least a) selecting a point directly on said surface S1; b) moving the tip of the probe to the distance d at the point selected in step a); and c) scanning the surface S1 with the probe from the point selected in step a) by maintaining the tip of the probe at the distance d and measuring the current in the probe as it scans; 6. The use according to claim 3, wherein the analysis of the surface S1 comprises positioning a scanning electrochemical microscopy probe at several points directly above the surface S1 to obtain the n 1 current values, the tip of the probe being positioned at a constant distance d from the surface S1 at each positioning point.
7. The use according to claim 6 , wherein the positioning points are selected randomly.
8. The analysis of the surface S1 comprises at least a) selecting a probe positioning point; and 8. Use according to claim 6 or claim 7, comprising the step of: b) for each positioning point, moving the tip of the probe a distance d and measuring the current with the probe at each positioning point.
9. 9. The use according to any one of claims 1 to 8, wherein an electrolyte is used which comprises a redox mediator in a reduced state.
10. 10. The use according to claim 9, wherein the redox mediator is ferrocyanide, ferrocene, decamethylferrocene, or ferrocenedimethanol.
Citation Information
Patent Citations
Scanning electrochemical microscope electrolytic cell for plate-shaped load sample corrosion research and application thereof
CN102928625A
Method and device for executing simultaneously electrochemical measurement and tunnel current measurement
JP1989141302A
Probe microscope and measurement method using the same
JP2010243355A